Proceedings Title: 2012 International Conference on Cyber Security, Cyber Warfare and Digital Forensic (CyberSec) 2012
DOI: 10.1109/cybersec.2012.6246096
|View full text |Cite
|
Sign up to set email alerts
|

Improving keystroke dynamics authentication system via multiple feature fusion scheme

Abstract: This paper reports the performance and effect of diverse keystroke features combination on keystroke dynamic authentication system by using fusion scheme. First of all, four types of keystroke features are acquired from our collected dataset, later then transformed into similarity scores by the use of Gaussian Probability Density Function (GPD) and Direction Similarity Measure (DSM). Next, three fusion schemes are introduced to merge the scores pairing with six fusion rules. Result shows that the finest perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…As the brief reviews in Section 2 were mentioned, Teh and colleagues' [24] research revealed that it would lead to the highest degree of discrimination when both the PR and RP times were regarded as keystroke dynamics of the users. Therefore, within the present study, based on the RP and PR times obtained in the enrollment phase, the CKD Table I.…”
Section: Proposed Keystroke Dynamics-based Authentication Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…As the brief reviews in Section 2 were mentioned, Teh and colleagues' [24] research revealed that it would lead to the highest degree of discrimination when both the PR and RP times were regarded as keystroke dynamics of the users. Therefore, within the present study, based on the RP and PR times obtained in the enrollment phase, the CKD Table I.…”
Section: Proposed Keystroke Dynamics-based Authentication Systemmentioning
confidence: 99%
“…In this work, the results of Teh and colleagues' [24] study is adopted for collecting the users' PR and RP times. Additionally, according to the suggestions of Campisi et al [20], users should enter the given numbers for five times.…”
Section: The Enrollment Phasementioning
confidence: 99%
See 1 more Smart Citation
“…zero to nine), in order to collect users' relative keystroke dynamics. In this work, the results of Teh et al's study [29] is adopted for collecting the users' PR and RP times. Additionally, according to the suggestions of Campisi et al [3], users should enter the given numbers for five times.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional keystroke dynamics include PR (Press-Release), PP (Press-Press), RP (Release-Press), and RR (Release-Release): In Teh et al's study [29], they conducted the related work on a variety of keystroke dynamics and analyzed various combinations of the four keystroke times (i.e., PR, PP, RP, and RR). The outcomes of the study reveal that it would lead to the best degree of discrimination by means of taking the PR and RP times as the keystroke dynamics of the specific user.…”
Section: Introductionmentioning
confidence: 99%